2021
DOI: 10.1111/aos.14851
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography angiography changes in cardiovascular systemic diseases and risk factors: A Review

Abstract: Cardiovascular (CV) disease (CVD) is the main cause of death around the world, and assessing a patient’s CV risk factors (CVRF) can play a major role in its prevention. Since it has been shown that retinal vascular alterations may reflect several systemic processes such as CVRF, we conducted a systematic review in order to summarize which ocular microvasculature changes can be found using Optical Coherence Tomography Angiography (OCTA) in patients without ocular diseases and with systemic pathologies/condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 64 publications
2
49
0
1
Order By: Relevance
“…Indeed, previous studies have already outlined, using arterial spin labeling MRI scans, the contribution of vascular factors in the detection of other neurodegenerative disorders, such as Alzheimer's disease, mild cognitive impairment, and Parkinson's disease [31,32]. Moreover, several studies reported the close relationship between the alterations in retinal perfusion by OCTA and the systemic vascular impairment involving cardiovascular and central nervous systems [33,34]. These results supported the hypothesis that retinal VD could represent a valid biomarker to detect the early systemic vascular damages.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, previous studies have already outlined, using arterial spin labeling MRI scans, the contribution of vascular factors in the detection of other neurodegenerative disorders, such as Alzheimer's disease, mild cognitive impairment, and Parkinson's disease [31,32]. Moreover, several studies reported the close relationship between the alterations in retinal perfusion by OCTA and the systemic vascular impairment involving cardiovascular and central nervous systems [33,34]. These results supported the hypothesis that retinal VD could represent a valid biomarker to detect the early systemic vascular damages.…”
Section: Discussionmentioning
confidence: 98%
“…In conclusion, the present study demonstrated that OCT is an objective method of diagnosis that can inform us about OSAS patients' clinical situations in an easy and noninvasive way by studying the retinal structure. As recent reviews also confirm [54,55], OCT could be useful for undertaking the follow-up of the treatment of this disorder, showing retinal changes that help to monitor endothelial dysfunction in OSAS, such as foveal thickness and the average thickness of retinal nerve fibers. In severe OSAS, retina thickness increased six months after treatment.…”
Section: Discussionmentioning
confidence: 90%
“…In conclusion, the present study demonstrated that OCT is an objective method of diagnosis that can inform us about OSAS patients' clinical situation in an easy and noninvasive way by studying the retinal structure. As recent reviews also confirm [40,41], OCT could be useful to undertake the follow-up of the treatment of this disorder, showing retinal changes that help monitor endothelial dysfunction in OSAS, such as foveal thickness and retinal nerve fibers average thickness. In severe OSAS, retina thickness increased six months after treatment.…”
Section: Discussionmentioning
confidence: 92%